Monitoring of Drug Planning and Procurement in Lubuk linggau City Health Department in 2021 - Mayel, M. Iqbal; Misnaniarti, Misnaniarti; Najmah, Najmah (Budapest International Research and Critics University, 2021)
For monitoring the planning and procurement of drugs, complete and accurate data and information are needed from the central, provincial, district and health facilities. Especially with the implementation of the JKN program, which has the potential to increase the need for drugs in health facilities. The purpose of the study is to describe the process of planning and procuring drugs from the health office and formulate solutions to increase the availability of drugs from the Lubuklinggau City Health Office. The methods of The research is qualitative. Then This research was conducted at the Pharmaceutical Technical Service Unit of the Lubuklinggau City Health Office with 10 informants. The research was conducted from October to November 2021 in the working area of the Lubuklinggau City Health Office. The results of the study were that it was found that the Pharmacy Installation and Public health center in the scope of the Lubuklinggau City Health Office in 2021 experienced a drug void. Furthermore, the planning process has been carried out by the Integrated Drug Planning Team but is not optimal. The drug procurement process uses the e-catalog method in accordance with the Decree of the Minister of Health of the Republic of Indonesia No. 1121/MENKES/SK/XII/2008. The conclusion is that drug management at the Lubuklinggau City Health Office has been in accordance with Kepmenkes No. 1121 of 2008 but has not been maximized. It is hoped that the Lubuklinggau City Health Office can accommodate all types of drugs rationally according to the drug needs of the public health center.